PENGARUH BAURAN PROMOSI TERHADAP VOLUME PENJUALAN PADA PT. VIVA VICTORY ABADI - Komarudin Komarudin; Hendro Setyono (Jurnal Fokus Manajemen Bisnis, 2016)
The purpose of this study was to determine the effect on promotion mix on  volume   sales  PT  Viva  Victory  Abadi.  Results  are  expected  to  be  a consideration for managers PT Viva Victory Abadi in determining the promotional mix  effect  on  sales  of  property,  as  well  as  using  some  other  variables  of  the promotion mix. The study was based on data usage all promotional costs incurred as well as the sale of the property from PT Viva Victory Abadi in the last two years. The  data  is  then  processed  using  multiple  linear  regression  method  in  SPSS.  The  results obtained prove not the absence of significant promotional mix on volume sales of PT Viva Victory Abadi.